Impact of proton radiotherapy on treatment timing in pediatric and adult patients with CNS tumors. Issue 6 (18th June 2020) - Jin, Michael C; Shi, Siyu; Wu, Adela; Sandhu, Navjot; Xiang, Michael; Soltys, Scott G; Hiniker, Susan; Li, Gordon; Pollom, Erqi L
Abstract: Background: Despite putative benefits associated with proton radiotherapy in the setting of CNS tumors, numerous barriers limit treatment accessibility. Given these challenges, we explored the association of proton use with variations in treatment timing. Methods: Pediatric and adult patients with histologically confirmed CNS tumors were identified from the National Cancer Database (2004-2015). Univariable and multivariable regression models were constructed to assess factors impacting radiation timing. Multivariable Cox regression was used to evaluate the effect of treatment delay on survival. Results: A total of 76 157 patients received photon or proton radiotherapy. Compared to photons, time to proton administration was longer in multiple pediatric (embryonal, ependymal, nonependymal glial, and other) and adult (ependymal, nonependymal glial, meningeal, other) tumor histologies. On adjusted analysis, proton radiotherapy was associated with longer delays in radiotherapy administration in pediatric embryonal tumors (+3.00 weeks, P = .024) and in all adult tumors (embryonal [+1.36 weeks, P = .018], ependymal [+3.15 weeks, P < .001], germ cell [+2.65 weeks, P = .024], glial [+2.15 weeks, P < .001], meningeal [+5.05 weeks, P < .001], and other [+3.06 weeks, P < .001]). In patients with high-risk tumors receiving protons, delays in adjuvant radiotherapy were independently associated with poorer survival (continuous [weeks], adjusted hazard ratio = 1.09, 95% CI = 1.02-1.16). Conclusions: Proton radiotherapy is associated with later radiation initiation in pediatric and adult patients with CNS tumors. In patients with high-risk CNS malignancies receiving protons, delayed adjuvant radiotherapy is associated with poorer survival. Further studies are needed to understand this discrepancy to maximize the potential of proton radiotherapy for CNS malignancies.